2019
DOI: 10.3390/su11123266
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Socio-Economic Impacts of Agricultural Subsidies: A Case Study from Bhutan

Abstract: As an agrarian nation, Bhutan’s agricultural policies prioritize agricultural subsidies to boost agricultural production, rural incomes, improve food security, and reduce income poverty, especially among the rural poor. However, the effectiveness and efficiency of such policy interventions remains unknown. Based on semi-structured interviews with heads of households from six blocks representing two districts, expert consultation with agricultural policymakers and extension agents, we attempted to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Wang et al [71] confirmed that agricultural subsidies are an important strategy to improve farm incomes and alleviate their poverty. However, their application is also very difficult given the socioeconomic dimensions of the receiving farms.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [71] confirmed that agricultural subsidies are an important strategy to improve farm incomes and alleviate their poverty. However, their application is also very difficult given the socioeconomic dimensions of the receiving farms.…”
Section: Discussionmentioning
confidence: 99%
“…In Bhutan, adequate infrastructural facilities and efficient extension services are indispensable for boosting the agriculture sector (Dendup, 2018). A study on the socio-economic impacts of agricultural subsidies in Bhutan indicates a large disparity in the provision of extension services between poor and non-poor populations, with poor farmers having less access to agricultural subsidies than non-poor populations (Wang et al, 2019). The study shows that none of the poor farmers received farm machinery, improved livestock such as Jersey cows and piglets, or biogas subsidies due to their inability to co-pay.…”
Section: Introductionmentioning
confidence: 99%
“…The need for state support of agriculture is explained by a number of reasons [7], and at the same time it is logical to assume that on the basis of these reasons, methodological approaches to assessing the effectiveness of implemented measures can be formed. Consider the main reasons for supporting agriculture based on the work of Minakov and Kuvshinov [8], and highlight the possible approaches to assessing the effectiveness of eliminating these causes with the help of state support measures (Table 2).…”
Section: Discussionmentioning
confidence: 99%